(untitled) (Al-Aasar, 2025)
The rapid expansion of artificial intelligence (AI) has significantly influenced the educational system across the globe. The current research illuminates the dual dimensions of university teacher’s perspectives regarding artificial intelligence and its resultant influence on occupational stress. Through a sample comprising N= 250 educators from a diverse array of public and private institutions within Punjab, the investigation employed established evaluative scales to assess attitudes and stress levels. The General Attitudes towards Artificial Intelligence Scale (Schepman & Rodway, 2020) and Teachers Occupational Stress Questionnaire (Hendres et al., 2014) were used. Data was analyzed using SPSS and the result showed a significant negative correlation between AI positivity and teacher occupation stress and no significant relationship between AI negativity and teacher occupational stress. The findings revealed that there were significant differences (i.e. gender and experiences) among teachers regarding artificial intelligence. The findings also revealed that teacher’s attitude towards AI significantly impacts their occupational stress. The findings of the study would be helpful for educators, instructors, administrators, and policymakers for a better understanding of teacher’s attitudes toward artificial intelligence. Furthermore, it suggests the need for targeted support and professional development programs to address these concerns and enhance teachers’ confidence in integrating AI into their teaching practices.